THE ROLE OF FINTECH AND FINANCIAL LITERACY ON MSME PERFORMANCE: Study on F&B MSMEs in Surabaya - Jamilah, Hesti Miftakhul; Mardiana, Lilik (UTSAHA: Journal of Entrepreneurship, 2024)
The role of fintech may pose a good impact on MSMEs and society in carrying out financial transactions and services digitally, easily and quickly. This requires improving inadequate financial literacy to encourage inappropriate financial decisions and avoid fraud or loss of funds from using fintech. This condition can play a big role for MSME players and society in economic growth which is able to apply digital technology well. The purpose of this study is to analyze and determine whether financial technology influences MSME players' financial literacy and performance, as well as how financial technology affects MSMEs' performance indirectly through financial literacy. This research sample was taken using purposive sampling, with the criteria being MSMEs that sell food and beverage products and those that have used financial technology products. There were 100 MSME units used as samples in the research obtained from the Surabaya City Cooperatives, SMEs and Trade Department. Research data collection uses a questionnaire and the data analysis technique for this research uses path analysis. The findings of the research indicate that financial literacy may moderate the impact of financial technology on the performance of food and beverage MSMEs in Surabaya and has a noticeable beneficial impact on MSMEs' performance. This explains that increasing adaptation to the use of financial technology needs to be supported by increasing financial literacy by MSME players to have the ability to enhance MSMEs' performance.